Surface modification of PVDF hollow fiber membrane to enhance hydrophobicity using organosilanes - Sairiam, Sermpong (2014)
This work investigates the membrane modification to enhance hydrophobicity aiming for applications as membrane contactors. The PVDF membranes were activated by NaOH and by plasma activation followed by grafting using three organosilanes. For the NaOH, the contact angle of original membranes (68°) was decreased from 44° to 31° with increasing NaOH concentration from 2.5M to 7.5M at 60°C for 3 h. The contact angle of NaOH treated membranes was increased to 100° after modification with 0.01M FAS-C8 for 24 h. A needle-like structure was observed on the membrane surface while there was no significant change in pore size and pore size distribution. Moreover, FTIR and XPS data showed Si peak and composition. The mechanical strength was improved. The surface modified membranes under helium plasma activation followed by grafting with 0.01M FAS-C8 for 24 h showed higher contact angle, mechanical strength and surface roughness than that obtained by NaOH activation method while other physical properties did not change. The long-term performance test for 15 days of operation was conducted. The modified membranes exhibited good stability and durability for CO2 absorption.